An Analysis of Factors Influencing the Students’ Learning English Achievement - Hiya Anisa; Arifmiboy Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2021)
The researcher conducted this study to reveal what factors were dominantly influencing the problem. The descriptive quantitative research used a total sampling technique which collects data through questionnaire. After collecting data from the questionnaire, the researchers identified the dominant factors that affect the English language skills of second grade students with a high average percentage. Based on the results of the study, it is shown that of the two factors that affect students' achievement in learning English, external factors are known with results (55.90%) and internal factors with results (54.40%). The dominant factor influencing the achievement of learning English in which the dominant is the external factor, namely the student's environmental factor, which was chosen by the respondents as much as 55.90%. Thus, it is concluded that external factors have a dominant influence on English learning achievement.